FORGE, Inc. examining the organization and its capability-building needs for policy advocacy - Cruz, Rizalino B. (2001)
Fellowship for Organizing Endeavors, Inc. (FORGE) exists to empower marginalized members of society. This sector constitutes the so-called "informal sector" that has no security of tenure, decent shelter and access to basic services such as water, shelter, livelihood and employment. FORGE hopes to empower this sector by making interventions in its cultural, spiritual, economic and political life. FORGE firmly believes it is addressing cultural, spiritual, economic and political aspects as seen in its effort s at community organizing and mobilization, the conduct of training, tactic, reflection sessions and the advocacy of alternative models such as gender sensitivity and community-based health care. Along with its efforts in alleviating poverty, FORGE has identified many capability-building needs for policy advocacy as reflected in its training needs survey: (a) program and project management (b) technical writing, (c) policy research and analysis, (d) policy advocacy, (e) resources generation and utilization, and (f) access to information and resources. These areas for improvement would definitely go a long way in helping FORGE confron the many faces of poverty and would help it advocate alternative development models. FORGE realized that there are certain requisites to be able to translate these good intentions into effective actions.
Keywords: Fellowship For Organizing Endeavors, Inc. (FORGE); Social advocacy; Policy advocacy; Urban poor; Nongovernmental organizations -- Case studies